شبكات التواصل الاجتماعي الفيسبوك وعلاقتها بالقيم لدى الطلبة الجامعيين دراسة ميدانية على عينة من طلبة جامعة الوادي - قدادرة, شوقي (University of Eloued جامعة الوادي, 2022)
يعد موضوع القيم وعلاقتها بالفيسبوك من أهم المواضيع التي تطرح عدة إشكاليات حول مصير هذه القيم بأنواعها مثل القيم الاجتماعية والأخلاقية، وعليه تمحورت إشكالية الدراسة حول: هل توجد علاقة بين استخدامات شبكات التواصل الاجتماعي“فيسبوك“ والقيم لدى الطلبة الجامعيين؟ ، وجاءت الفرضية العامة عن النحو التالي: هناك علاقة ذات دلالة إحصائية بين إستخدام شبكات التواصل الاجتماعي ”فيسبوك ” القيم لدى الطلبة الجامعيين، وإتبعنا خطة مقسمة إلى قسمين نظري و ميداني على عينة من طلبة جامعة الوادي. وخلصت الدراسة الى النتائج التالية أهمها: ان استخدام الفيسبوك له مساهمة وعلاقة مع القيم الأخلاقية لدى الطالبة الجامعيين ولكن بشكل متوسط وذلك بمتوسط حسابي (3.3174)، ان استخدام الفيسبوك له مساهمة وعلاقة مع القيم الاجتماعية لدى الطالبة الجامعيين ولكن بشكل متوسط وذلك بمتوسط حسابي (3.44457). The topic of values and its relationship with Facebook is one of the most important topics that raise several problems about the fate of these types with all kinds, such as social and moral values. Therefore, the problem of study revolves around: Is there a relationship between the uses of social networks “Facebook” and the values of university students? The general hypothesis came as follows: There is a statistically significant relationship between the use of social networks “Facebook” values among university students, and we followed a plan divided into two theoretical and field sections on a sample of Valley students. The study concluded:The following are the most important results: The use of Facebook has a contribution and relationship with the moral values of the undergraduates, but on an average basis, according to an arithmetic mean (3.3174).The use of Facebook has a contribution and relationship with the social values of the undergraduates, but in an average way, according to an average of (3.44457).
مقال